1995
DOI: 10.1007/bf01844822
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating gunshots to the head and lack of immediate incapacitation II. Review of case reports

Abstract: Because of the enhanced intracranial tissue disruption (see companion paper) and the functional significance of the central nervous system, penetrating gunshot wounds of the head commonly result in immediate incapacitation. However, in the last century numerous publications reported sustained capability to act following penetrating gunshot wounds of the head. These are reviewed. A large number of case reports had to be excluded from re-examination because of doubtful capability to act or lack of morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 30 publications
0
24
0
6
Order By: Relevance
“…Of course, the additional wounding capacity of muzzle-gas pressure depends on the load of the cartridge. Karger [19] published a review of suicidal gunshot wounds to the head where a lack of incapacitation was observed, especially concerning cartridges of low-gas pressure with .22, .25 or .32 calibres. Still, there are cases of successful suicides with blank cartridge guns pressed against the head [20].…”
Section: Discussionmentioning
confidence: 98%
“…Of course, the additional wounding capacity of muzzle-gas pressure depends on the load of the cartridge. Karger [19] published a review of suicidal gunshot wounds to the head where a lack of incapacitation was observed, especially concerning cartridges of low-gas pressure with .22, .25 or .32 calibres. Still, there are cases of successful suicides with blank cartridge guns pressed against the head [20].…”
Section: Discussionmentioning
confidence: 98%
“…turcica, where significant amount of energy has been absorbed [6,7]. The variation between scores is due to the simple fact that this type of study cannot be carried out in controlled laboratory conditions.…”
Section: Discussionmentioning
confidence: 98%
“…rifles). However, death in cases of low energy projectile can be instantaneous, if the vital structures of the brain stem are damaged [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Lesões de órgãos torácicos produzidas por projéteis de uso civil, mesmo considerando a transfixação do coração, da porção torácica da artéria aorta ou do tronco pulmonar, normalmente não causam parada circulatória imediata, ainda que sejam lesões que produzirão incapacitação e que serão geralmente fatais [6,[23][24][25]. Ou seja, ao contrário do "senso comum" e do que é representado em filmes e seriados de televisão, uma lesão cardíaca transfixante por projétil de arma de fogo (PAF) de uso civil ainda permite que a vítima execute movimentos por um período mínimo de 10 segundos, o suficiente para efetuar um ou mais disparos com uma AF [6,[24][25].…”
Section: Discussionunclassified
“…Fisiologicamente, apenas lesões no sistema nervoso central (SNC) causam incapacidade motora imediata, desde que envolvam regiões encefálicas específicas, como a porção cervical alta da medula espinal, o tronco encefálico (mesencéfalo, ponte ou bulbo), o diencéfalo e áreas extensas do córtex cerebral [6,[23][24][25]. Ressalta-se que lesões dessas regiões mais nobres do SNC também podem ocorrer sem que o projétil as atinja diretamente, através da transmissão radial de energia produzida pela cavitação temporária dos projéteis [30].…”
Section: Discussionunclassified